Produksi dan Kualitas Beras Dua Varietas Padi Akibat Rebah dan Terendam - . Dulbari; Edi Santosa; Eko Sulistyono; Herdhata Agusta; Dwi Guntoro; Sofyan Zaman; Yonny Koesmaryono (Institut Pertanian Bogor, 2018)
Rice lodging followed by flooding has negatively detriment on the production, however, scientific evident is still rare. As the incident tends to escalate as the impact of extreme weather, hence, research was conducted in order to evaluate rice production and its quality of two rice genotypes treated with lodging-flooding. The experiment was conducted at Leuwikopo Farm IPB Bogor in July-October 2016 using randomized complete block design using two factors, i.e., variety (Way Seputih and Way Apo Buru) and lodging (no lodged [bending 0-18°], lodged [lodged 38-56°], and lodged with flooded [lodged 76-90°]). Rice hill aged 85 days after transplanting was lodged for 15 days. Results showed that lodged with flooded treatment did not increase yield loss although the plant tended to have sterility 5.59-22.00% higher, grain weight 2.05-35.26% lower, and 0.88-10.66% lower value of rice to unhusked ratio. Grains from the lodged-flooded plant had a number of head rice 13.38-15.78% lower, broken rice 0-24.84% higher, and stimulated germination on 1.33-3.40% grains than lodged-without-flooded. It is important to use rice varieties with stable on milling quality to address the lodged-flooded incident.